2013
DOI: 10.1021/ie302274e
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Modified Polyimide Fiber-Filled Ethylenepropylenediene Monomer Insulations for a Solid Rocket Motor: Processing, Morphology, and Properties

Abstract: Polyimide (PI) short fiber-filled ethylenepropylenediene monomer (EPDM) insulations for a solid rocket motor were fabricated by surface modification of PI short fibers in an alkaline aqueous solution and subsequently by mixing formulation of EPDM insulations on a two-roll mill. The effects of PI short-fiber surface modification and short-fiber content on the mechanical and ablative properties were investigated. The excellent mechanical and ablative properties of PI fiber-filled EPDM insulations were based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…Rajeev et al [41] reported the study of EPDM reinforced with melamine fibers [13], [42]. Han et al [43] also reported the use of polyimide (PI) short fiber-filled EPDM insulators: PI fibers exhibited high thermal stability and char yield because of their stiff aromatic backbones and the aromatic imide groups of the molecular main chains [44]- [47].…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Rajeev et al [41] reported the study of EPDM reinforced with melamine fibers [13], [42]. Han et al [43] also reported the use of polyimide (PI) short fiber-filled EPDM insulators: PI fibers exhibited high thermal stability and char yield because of their stiff aromatic backbones and the aromatic imide groups of the molecular main chains [44]- [47].…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…It has been reported that the thermal stability and the carbon residue of PBO fibers under nitrogen at 1 000 °C are much higher than Aramid fiber . According to Gao et al if compared to traditional EPDM/Aramid ablatives, the erosion rate as well as the loss of mass of the EPDM/Zylon was lower than 50 wt% Han et al also reported the use of polyimide (PI) short fiber‐filled EPDM insulators. Compared with Aramid fibers, polyimide fibers exhibited better thermal stability and higher char residues because of their stiff aromatic backbones and aromatic imide groups of the molecular main chains. The use of new generation, nanostructured EHSMs could also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Aramid pulp (Twaron 1099) was supplied by Teijin. The amount of pulp used to compound the tested formulation was set to 10 phr since this percentage typically tends to produce the best compromise between the mechanical and ablative properties of EPDM based EHSMs . Nanosilica particles (R7200 grade, kindly supplied by Evonik) was used to increase the ablation resistance of the material: according to our experience and to the wide literature on EPDM based EHSMs, 20 phr of nanosilica resulted to be a proper amount of silica able to produce good ablative properties .…”
Section: Methodsmentioning
confidence: 99%
“…Elastomeric polymer ablative materials (EPAM) are often adopted as the thermal protection layer inside rocket chamber due to its tolerance to thermal stresses which may lead to crack in the ablative materials [1]. Ethylene-propylene-diene terpolymer [2,3], nitrile-butadiene rubber (NBR) [4], styrene butadiene rubber [5], silicon rubber [6] and silicon containing rubber [7] have been studied as the matrix for EPAM. However, rubbers have poor ablation resistance, and fillers and fibers are required to reinforce them.…”
Section: Introductionmentioning
confidence: 99%
“…So, they are seldom used in EPAM, but have applications in rigid ablative materials through an impregnation method [11e13]. Flexible fibers with good thermal stability were employed as the reinforcement for EPAM, such as aramid fibers (AF) [14], poly(p-phenylene-2,6-benzobisoxazole) fibers [2], melamine fibers [4], polyimide fibers [3], polysulfonamide pulp [15], kynol fiber and Kevlar pulp [16].…”
Section: Introductionmentioning
confidence: 99%